The short-term survival following acute myocardial infarction: A prospective observational study - Mohammad Aryaie; Fozieh Bakhsha; Seyyed Yaghub Jafari; Zahra Yousefi; Ali Reza Heidari; Zahra Esmaeili; Sakineh Sobhani; Shima Aghili (Journal of Basic Research in Medical Sciences, 2017)
Introduction: To investigate 28 days survival rate following first acute myocardial infarction (AMI) associated with the presence of classical risk factors and treatment modalities in Gorgan, north of Iran.